2020
DOI: 10.1177/2056305120909474
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Oneself on YouTube: Teenage Peer Socialization and Social Recognition Processes

Abstract: YouTube is the preferred online platform for today’s teenagers. As such, this article explores the relationship between socialization processes in adolescent peer culture and the meanings behind the production and reception of YouTube videos by teenage audiences. Two fields of enquiry comprise the data analyzed in this article. First, through content analysis, we studied the production of videos on YouTube by teenagers between the ages of 14 and 18. The discursive construction of an audience is expressed by Yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 50 publications
2
27
0
4
Order By: Relevance
“…YouTube, Wikipedia, Spotify, and Pinterest were examples of these platforms at the time of study. Users frequently access these platforms to see themselves reflected in content created by others, and this content can be an important component of identity development, socialization, and social recognition processes (Balleys et al, 2020;Lewallen & Behm-Morawitz, 2016). Again, the commercialization of mainstream social media has altered user patterns and behaviors, although possibly not to the same extent as in the first two categories (Schwemmer & Ziewiecki, 2018).…”
Section: Content Consumption Platformsmentioning
confidence: 99%
“…YouTube, Wikipedia, Spotify, and Pinterest were examples of these platforms at the time of study. Users frequently access these platforms to see themselves reflected in content created by others, and this content can be an important component of identity development, socialization, and social recognition processes (Balleys et al, 2020;Lewallen & Behm-Morawitz, 2016). Again, the commercialization of mainstream social media has altered user patterns and behaviors, although possibly not to the same extent as in the first two categories (Schwemmer & Ziewiecki, 2018).…”
Section: Content Consumption Platformsmentioning
confidence: 99%
“…From the sociological perspective, themes related to socialisation processes in adolescent peer culture (Balleys et al 2020) and the framing of socially meaningful content (Keskin 2018;Thelwall 2018) dominate. Issues of business relationship formation (Vonderau 2016) and the specificity of users' online behaviour are also raised (Misoch 2014).…”
Section: Youtubementioning
confidence: 99%
“…In [1] it was reported that the main reasons adolescent use social media is for information sharing, alleviating boredom, escapism, to interact socially with peers, building social capital and to receive feedback on their appearances. Therefore, adolescents' participation in social media platforms is an important aspect for "social participation" [1][2][3][4]. However, research has also shown that social media use can have an impact on the emotional state of the adolescent and the extent to which they can be influenced by peers [5].…”
Section: Introductionmentioning
confidence: 99%
“…In [3] it was shown that adolescents develop a familiarity with the YouTubers (both as content creators and viewers) as they can identify with what they represent. This prolific use of YouTube by adolescents, and even pre-adolescent children, expose children to a variety of content: good and bad.…”
Section: Introductionmentioning
confidence: 99%